Pengaruh Penggunaan Media Pembelajaran Strip Story Terhadap Hasil Belajar Al-Qur’an Hadist Siswa di MTSN 6 Agam - Yulfamita, Linda (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research was motivated by the demand for teachers to be able to use a variety of learning media, besides that student learning outcomes were not optimal and students tended to play around while learning was taking place. So that this can have an impact on student learning outcomes. Based on these problems, it is necessary to make efforts to improve student learning outcomes by implementing the Strip Story learning media. This research aims to determine the effect of using strip story media on student learning outcomes in the Al-Qur’an Hadith class IX subject at MTsN 6 Agam. This research is quantitative research with experimental methods. The design used is a posttest only control design. The population in this study was 3 groups of class IX MTsN 6 Agam students, while the sample was taken from a cluster random sampling technique and class IX.7 was selected as the experimental class and IX.8 as the control class. This research consists of 2 variables, namely strip story media (X) as the independent variable and student learning outcomes (Y) as the dependent variable. The data collection technique used was a test in the form of multiple choice questions with 20 questions. The data analysis used was a paired simple test. The results of the research show that there is an influence of the use of strip story learning media on learning outcomes. This can be seen from the significant value of 0.000 which is smaller than 0.05. And also by looking at the average value for the experimental class of 86.41 and for the control class the average value was 84.38. Based on the results above, it can be concluded that the class that applies strip story media has a higher average score when compared to the average value of the class that does not apply learning media.